Error Analysis On The Use Of Past Tense In Writing Recount Text A Case Study At The Second Year Students Of Madrasah Tsanawiyah Darul Ishlah Ireng Lauq At The Academic Year 2013/2014 - Suparlan Suparlan (JUPE : Jurnal Pendidikan Mandala, 2019)
The writer is interested in investigating the error analysis in using past tense in writing recount text a case study at the second year students of Madrasah Tsanawiyah Darul Ishlah Ireng Lauq at the academic year 2013/2014. The problem of the present study is limited in on the use of past tense in writing recount text. On the other hand, the general objective of the writing is to analyze the use of past tense in writing recount text. The specific objective is to know the students ability in using the past tense especially in writing recount text.The population of the study includes all students who have been studying at the second year of Madrasah Tsanawiyah Darul Ishlah Ireng Lauq at the academic year 2013/2014.The instrument of data collection is only one test. The test type/ part namely slot test. The test is confined to use the simple past tense. The data is analyzed by descriptive quantitative method. From the result of this analyze, the writer concludes the second year of the students of Madrasah Tsanawiyah Darul Ishlah Ireng Lauq at the academic year 2013/ 2014 has difficulty in identifying the past tense. This analyze shown that they make errors in using auxiliary did, errors in using verbs and other errors. Finally not only auxiliary did or verb as the specific study had most errors but also another errors appear without they realize, it happened because the lack of mastery in structure of past tense one of the tense in English.